Extraction of The Chemical Components of Dengen Leaves (Dillenia serrata Thunb) by MAE Method and Activity Test as Antioxidant and Toxicity - Wela, Nasriadi Dali; Dali, Seniwati; Chairunnas, Armadi; Amalia, Hilda Ayu Melvi; Puspitasari, Sri Ayu Andini (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2022)
Research on the extraction of chemical components of Dengen (Dillenia serrata Thumb) leaves using the MAE (microwave-assisted extraction) method and activity as an antioxidant and toxicity test has been carried out. This study aimed to extract the chemical components of Dengen leaves using the MAE method and to test the antioxidant activity and toxicity of the ethanol extract of Dengen leaves. The chemical components of Dengen leaves were extracted by the MAE method and obtained ethanol extract with a yield of 47%. Dengen leaves ethanol extract was partitioned with n-hexane and ethanol as solvents and obtained yields of 5% (n-hexane) and 65% (ethanol). The chemical components of Dengen leave ethanol extract were identified by phytochemical screening. The results of phytochemical screening showed the presence of secondary metabolites of alkaloids, flavonoids, saponins, polyphenols, terpenoids, and steroids. The antioxidant activity test of the ethanol extract of Dengen leaves was carried out using the DPPH (2,2-diphenyl-1-picrihydrazil) method and obtained the value of IC50 = 100,363 ppm (strong antioxidant). A toxicity test of the ethanol extract of Dengen leaves was carried out using the BSLT (Brine Shrimp Lethality Test) method and obtained the value of LC50 = 18.3443 ppm (very toxic).